COMPUTATIONAL LINGUISTICS AND ARTIFICIAL INTELLIGENCE - Affas MAAMAR & Hadjer HADJCHERIF (Ziglôbitha)
Abstract : Computational linguistics, as an interdisciplinary field combining linguistics and computer science, aims to enable computers to process natural language. It emerged in the twentieth century with the advancement of computer science, with its earliest experiments dating back to the 1950s. This field encompasses both theoretical and applied aspects, drawing on artificial intelligence, neural networks, algorithms, Markov chains, and statistical methods to model human language. This study explores the origins and applications of computational linguistics, highlighting the crucial role of interdisciplinary approaches, which are essential for addressing the complex challenges of language processing, particularly in the context of the Arabic language.